Discover answers to your most pressing questions at Westonci.ca, the ultimate Q&A platform that connects you with expert solutions. Get quick and reliable solutions to your questions from knowledgeable professionals on our comprehensive Q&A platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
Certainly! Let's solve the given exponential equation step-by-step:
We are given:
[tex]\[ 2^x + 2^{-x} = \frac{5}{2} \][/tex]
### Step 1: Substitution
Let us substitute [tex]\( y = 2^x \)[/tex]. Consequently, [tex]\( 2^{-x} = \frac{1}{2^x} = \frac{1}{y} \)[/tex]. The equation becomes:
[tex]\[ y + \frac{1}{y} = \frac{5}{2} \][/tex]
### Step 2: Clear the Fraction
To clear the fraction, multiply every term by [tex]\( y \)[/tex]:
[tex]\[ y^2 + 1 = \frac{5}{2}y \][/tex]
### Step 3: Rearrange into Standard Quadratic Form
Rearrange the equation to get it into the standard quadratic form [tex]\( ax^2 + bx + c = 0 \)[/tex]:
[tex]\[ 2y^2 - 5y + 2 = 0 \][/tex]
### Step 4: Solve the Quadratic Equation
We can solve the quadratic equation using the quadratic formula, [tex]\( y = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \)[/tex], where [tex]\( a = 2 \)[/tex], [tex]\( b = -5 \)[/tex], and [tex]\( c = 2 \)[/tex]:
[tex]\[ y = \frac{-(-5) \pm \sqrt{(-5)^2 - 4 \cdot 2 \cdot 2}}{2 \cdot 2} \][/tex]
[tex]\[ y = \frac{5 \pm \sqrt{25 - 16}}{4} \][/tex]
[tex]\[ y = \frac{5 \pm \sqrt{9}}{4} \][/tex]
[tex]\[ y = \frac{5 \pm 3}{4} \][/tex]
This gives us two solutions for [tex]\( y \)[/tex]:
[tex]\[ y = \frac{5 + 3}{4} = \frac{8}{4} = 2 \][/tex]
[tex]\[ y = \frac{5 - 3}{4} = \frac{2}{4} = \frac{1}{2} \][/tex]
### Step 5: Back-substitute [tex]\( y = 2^x \)[/tex]
Now, recall that [tex]\( y = 2^x \)[/tex], so we substitute back to find [tex]\( x \)[/tex].
For [tex]\( y = 2 \)[/tex]:
[tex]\[ 2^x = 2 \][/tex]
By inspection, [tex]\( x = 1 \)[/tex].
For [tex]\( y = \frac{1}{2} \)[/tex]:
[tex]\[ 2^x = \frac{1}{2} \][/tex]
[tex]\[ 2^x = 2^{-1} \][/tex]
By inspection, [tex]\( x = -1 \)[/tex].
### Step 6: State the Solutions
So, the solutions to the equation [tex]\( 2^x + 2^{-x} = \frac{5}{2} \)[/tex] are:
[tex]\[ x = -1 \][/tex]
[tex]\[ x = 1 \][/tex]
Therefore, the values of [tex]\( x \)[/tex] that satisfy the given equation are:
[tex]\[ x = -1 \quad \text{and} \quad x = 1 \][/tex]
We are given:
[tex]\[ 2^x + 2^{-x} = \frac{5}{2} \][/tex]
### Step 1: Substitution
Let us substitute [tex]\( y = 2^x \)[/tex]. Consequently, [tex]\( 2^{-x} = \frac{1}{2^x} = \frac{1}{y} \)[/tex]. The equation becomes:
[tex]\[ y + \frac{1}{y} = \frac{5}{2} \][/tex]
### Step 2: Clear the Fraction
To clear the fraction, multiply every term by [tex]\( y \)[/tex]:
[tex]\[ y^2 + 1 = \frac{5}{2}y \][/tex]
### Step 3: Rearrange into Standard Quadratic Form
Rearrange the equation to get it into the standard quadratic form [tex]\( ax^2 + bx + c = 0 \)[/tex]:
[tex]\[ 2y^2 - 5y + 2 = 0 \][/tex]
### Step 4: Solve the Quadratic Equation
We can solve the quadratic equation using the quadratic formula, [tex]\( y = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \)[/tex], where [tex]\( a = 2 \)[/tex], [tex]\( b = -5 \)[/tex], and [tex]\( c = 2 \)[/tex]:
[tex]\[ y = \frac{-(-5) \pm \sqrt{(-5)^2 - 4 \cdot 2 \cdot 2}}{2 \cdot 2} \][/tex]
[tex]\[ y = \frac{5 \pm \sqrt{25 - 16}}{4} \][/tex]
[tex]\[ y = \frac{5 \pm \sqrt{9}}{4} \][/tex]
[tex]\[ y = \frac{5 \pm 3}{4} \][/tex]
This gives us two solutions for [tex]\( y \)[/tex]:
[tex]\[ y = \frac{5 + 3}{4} = \frac{8}{4} = 2 \][/tex]
[tex]\[ y = \frac{5 - 3}{4} = \frac{2}{4} = \frac{1}{2} \][/tex]
### Step 5: Back-substitute [tex]\( y = 2^x \)[/tex]
Now, recall that [tex]\( y = 2^x \)[/tex], so we substitute back to find [tex]\( x \)[/tex].
For [tex]\( y = 2 \)[/tex]:
[tex]\[ 2^x = 2 \][/tex]
By inspection, [tex]\( x = 1 \)[/tex].
For [tex]\( y = \frac{1}{2} \)[/tex]:
[tex]\[ 2^x = \frac{1}{2} \][/tex]
[tex]\[ 2^x = 2^{-1} \][/tex]
By inspection, [tex]\( x = -1 \)[/tex].
### Step 6: State the Solutions
So, the solutions to the equation [tex]\( 2^x + 2^{-x} = \frac{5}{2} \)[/tex] are:
[tex]\[ x = -1 \][/tex]
[tex]\[ x = 1 \][/tex]
Therefore, the values of [tex]\( x \)[/tex] that satisfy the given equation are:
[tex]\[ x = -1 \quad \text{and} \quad x = 1 \][/tex]
Thank you for trusting us with your questions. We're here to help you find accurate answers quickly and efficiently. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.